Visible Fat Content of Hotpot Beef Acceptability by New Zealand Chinese, Japanese, and Korean Consumers - M. M. Farouk; M. Staincliffe; D. L. Hopkins; G. Wu; C. Che; A. E. D. Bekhit; M. J. Y. Yoo; A. Horita; G. Urquiola; C. Craigie; K. Taukiri; R. Zhang; et al. (Journal of Food Quality)
Hotpot meat is a popular way of meat consumption in some Asian countries. This study was carried out to investigate the effect of visible fat content on consumer acceptability of hotpot meat. Hotpot beef with six visible fat levels (11%–35%) was produced and digitally photographed, and the images were ranked by panels of New Zealand Chinese (110), Japanese (145), and Korean (118) consumers. For all the nationalities, a preference for visible fat was influenced by both gender and age. The Chinese preferred the visibly fattiest hotpot beef, whereas the Koreans preferred the leanest with the Japanese preferring the two fat extremes equally. For individuals in the age range of 19–30 years, both Chinese males and females preferred the higher fat meat (35%), while their Japanese and Korean counterparts preferred the second visibly leanest (14%). For those over 50 years, Chinese females preferred the lower fat meat compared to their male counterparts, whereas there was no gender difference at this age for the Japanese and Koreans preference for the visibly lean hotpot beef. This study indicates that there are subtle differences between nationalities in terms of their preference for the fat content of hotpot beef that may have implications in meat merchandising, product development, and health policies.